2020
DOI: 10.1074/jbc.ra119.011006
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 regulates antibody-dependent intracellular neutralization of viruses via deacetylation of TRIM21

Abstract: Tripartite motif-containing protein 21 (TRIM21) is a cytosolic antibody receptor that targets the internalized virus-antibody complex to the proteasome for degradation. However, the precise mechanism regulating TRIM21 activity is unknown. Here we show that TRIM21 is a substrate of histone deacetylase 6 (HDAC6) and that its function is regulated by acetylation. HDAC6 interacts with TRIM21 through its PRYSPRY motif and deacetylates TRIM21 at lysine 385 and lysine 387, thus promoting its homodimerization. Inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, including rheumatoid arthritis, Systemic lupus erythematosus, and Sjogren’s syndrome ( Schulte-Pelkum et al, 2009 ). TRIM21 acts as an important factor involved in the innate immune responses against microbial infection, including bacterial, viral, and parasite ( Hos et al, 2020 ; Mu et al, 2020 ; Xie et al, 2020 ), however, little about TRIM21 is known for parasites infection. In this study, we reported that T. gondii RH and CEP infection upregulated the expression of TRIM21, thus restricted parasite replication through NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, including rheumatoid arthritis, Systemic lupus erythematosus, and Sjogren’s syndrome ( Schulte-Pelkum et al, 2009 ). TRIM21 acts as an important factor involved in the innate immune responses against microbial infection, including bacterial, viral, and parasite ( Hos et al, 2020 ; Mu et al, 2020 ; Xie et al, 2020 ), however, little about TRIM21 is known for parasites infection. In this study, we reported that T. gondii RH and CEP infection upregulated the expression of TRIM21, thus restricted parasite replication through NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we interrogated the transcriptome of COPS3-inactivated embryos. It is reassuring that the number of mRNAs which were perturbed by the microinjection of the sole Trim21 mRNA was very small, given the known interaction partners of TRIM21, for example, the gap-junction subunit CONNEXIN 43 48 , the tumor suppressor p53 49 or the histone deacetylase HDAC6 50 . By contrast, the transcriptome was vastly perturbed -including 'housekeeping' mRNAs -after COPS3 inactivation, and such vastness requires an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled protein stability caused by aberrant ubiquitination/deubiquitination is usually associated with tumorigenesis and progression. [30][31][32] For example, loss-of-function mutation of tumor suppressor genes encoding the E3 ligase Von Hippel-Lindau syndrome, or the deubiquitylase cylindromatosis, has been implicated in several types of cancer. 16 USP21 has a dual role in tumorigenesis, largely determined by its substrate to be oncogenic or tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%